Perilaku Hidup Bersih Dan Sehat Di Panti Asuhan Solaya (PASO) - Penuli Malida Putri; Juan Frido Manihuruk (Yayasan Literasi Sains Indonesia, 2022)
Clean and Healthy Life Behavior (PHBS) is all health behavior that is carried out with awareness so that family or family members can help themselves in the health sector and play an active role in activities in the community. Clean and Healthy Life Behavior (PHBS) is behavior related to the efforts or activities of a person to maintain and improve his health. Clean and Healthy Living Behavior (PHBS) is a real embodiment of the healthy paradigm in the culture of living for individuals, families and communities that is health-oriented, aiming to improve, maintain and protect their health. Clean and Healthy Life Behavior is all health behavior that is carried out with awareness so that family or family members can help themselves in the health sector and play an active role in health activities in the community.The form of community empowerment that is aware, willing, and able to practice PHBS includes 5 priority programs, namely MCH, Nutrition, Environmental Health, Lifestyle, Health Fund/Health Insurance/JPKM. It is hoped that the community's Clean and Healthy Living Behavior (PHBS) can support efforts to achieve the 2010 Healthy Indonesia program. One of the indicators of Clean and Healthy Lifestyle Behavior is Hand Washing with Soap (CTPS). The expected result is an increase in public knowledge about the importance of washing hands with soap to prevent various diseases and increasing the community's ability to wash hands properly and correctly.